Reading Sami Moisio’s Geopolitics of the Knowledge-Based Economy - Sellar, Christian; Jones, Martin; Wang, June; Gaffney, Christopher; Kuus, Merje; Painter, Joe; Adams, Paul C.; Moisio, Sami (Political Geography, 2022)
Peer reviewed